Observation of surface isocyanate formation on the CeO2 and on Rh supported by CeO2 - Süli-Zakar Tímea (2013)
Infrared spectroscopic studies showed the formation of isocyanate surface complex in the NO + CO reaction on supported noble metal catalysts. As this surface complex plays decisive role in the undersived side reaction of the catalytic transformation of the auto exhaust gases, great attention should be payed to its properties and to the mechanism of its formation. For this purpose the interaction of NO + CO gas mixture with supported gold, palladium and rhodium catalysts was investigated.When the adsorption and reaction of NO with CO two absorption bands appeared in the FTIR spectra of Rh/Ce02 at 2180 and 2210 cm"1 , which were not observed following the adsorption of reactants and products. Adsorption of isocyanate acid on pure Ce02 yielded the same spectral features suggesting that these bands belong to adsorbed isocyanate, NCO, species bonded to the Ce02 . These results suggest that spillover process of NCO from the Rh onto support proceeds even in the case of Ce02 used as a solid oxidizer in the three-way catalyst. NCO attached to ceria reacts with H2 0 resulting in the release of NH3.
Keywords: Természettudományok; Kémiai tudományok